Monte Carlo investigation of hysteresis properties in ferroelectric thin-films under the effect of uniaxial stresses - Y. Laosiritaworn (2018)
The uniaxial stress dependence of the hysteresis behavior of ferroelectric films was studied. The DIFFOUR model was modified to include the uniaxial stress effect. Both the uniaxial stress and the external electric field were applied on the out-of-plane direction of the films. The polarization was measured with varying the magnitude of the applied stress and the electric field frequency via the dynamics of the polarization reversal in terms of hysteresis. The study was taken by means of Monte Carlo simulations using the spin-flip Metropolis algorithm. From the results, the district dependence of hysteresis behavior on frequency between low frequency and high frequency was prominent. On the other hand, the remanent and the coercivity significantly decreased with increasing applied stresses. Moreover, the areas under the hysteresis loops also decreased indicating smaller magnitude of energy dissipation. The results agree well with related experiments where applicable. © 2008 Elsevier Ltd and Techna Group S.r.l.